Trends in management and outcome of acute coronary syndrome in women ≥80 years versus those <80 years in Israel from 2000–2016. (15th April 2019) - Rubinstein, Roy; Matetzky, Shlomi; Beigel, Roy; Iakobishvili, Zaza; Goldenberg, Ilan; Shechter, Michael; ,
Abstract: Background: While women ≥80 years old have a high prevalence of coronary artery disease (CAD), little data exist regarding their outcome following acute coronary syndrome (ACS). Methods: In a retrospective study based on data of 3518 ACS women patients who were enrolled in the ACS Israel Survey (ACSIS), we first evaluated and compared the clinical outcomes of 858 ACS women ≥80 years with 2660 ACS women <80 years, hospitalized during 2000–2016. Secondly, we evaluated the clinical outcome of 450 women ≥80 years hospitalized during 2000–2006 ('early period') and compared them with 408 ACS women of the same age group hospitalized during 2008–2016 ('late period'). Results: Implementation of the ACS AHA/ACC/ESC therapeutic guidelines was lower in ACS women ≥80 years compared with women <80 years. Multivariate Cox regression analysis demonstrated a worse 1-year survival rate in the ACS women ≥80 years compared with those <80 years. During the late period women ≥80 years were treated more frequently with guideline-recommended therapies compared with patients from the same age group who were hospitalized in the early period. A significant decline in in-hospital mortality rates in ACS women ≥80 years hospitalized in the late compared with the early period was demonstrated. However, 7-day, 30-day and 1-year mortality rates were not significantly changed. Conclusion: Adverse outcome rates of ACS women ≥80 years were significantly higher compared with those <80 years. In-hospital survival rates of ACS women patients ≥80 years improved during the 2000–2016 period; however, long-term survival rates were not significantly changed. Highlights: Relatively low rates of in-hospital guideline-recommended therapies are utilized for the treatment of ACS elderly women. ACS women ≥80 years have 2–3 fold higher mortality rates compared with those <80 years. An increase in the use of in-hospital guideline-recommended therapies in elderly women was detected during 2000–2016. Improvement was detected in short-term, but not in long-term mortality rates in elderly women during 2000–2016. Shorter overall pre-treatment delays plus cardiac rehabilitation participation may improve outcomes of elderly ACS women.